High-reliability polymer dielectric material and planar capacitor material and manufacturing method thereof
By using negative pressure treatment technology to remove air pores in the dielectric layer of the chip capacitor material, the problems existing in air pores in the dielectric layer are solved, and the voltage withstand characteristics of the capacitance material and the reliability of electronic products are improved.
Patent Information
- Application Number
- CN202411302529.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-17
AI Technical Summary
In the production process of chip capacitor materials, it is difficult to avoid the presence of pores in the dielectric layer, resulting in a degradation of capacitance performance and affecting the reliability and function of electronic products.
Using a high-reliability polymer dielectric material production method, by providing inorganic fillers, matrix materials, additives and solvents, polymer dielectric materials are formed and processed in a negative pressure environment to remove bubbles, reduce or eliminate them. Air pores in the dielectric layer.
It effectively reduces the number of pores in the dielectric layer of the chip capacitor material, improves the voltage withstandability and reliability of the capacitor material, and improves the performance of electronic products.
Smart Images

Figure CN119320589A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of capacitor technology, and in particular to a high-reliability polymer dielectric material and a planar capacitor material and a manufacturing method thereof. Background Art
[0002] Due to factors such as low precision of production equipment and imperfect production process, it is difficult to achieve pore-free dielectric layer due to objective conditions such as fluidity of dielectric layer slurry and volatilization of solvent in pre-baking process (non-vacuum air flotation pre-baking oven) of dielectric layer slurry in the production process of chip capacitor materials. If there are pores in the insulating dielectric layer, it is equivalent to that there should be only one insulating dielectric layer but also contains air (or vacuum) medium, which will inevitably change the capacitance performance of the chip capacitor material (such as reduced withstand voltage characteristics, reduced capacitance value, reduced peel strength, etc.), thereby reducing the reliability of electronic products and even causing electronic products to fail. In view of this, reducing the pores in the dielectric layer of chip capacitor materials or eliminating the pores in the dielectric layer is a technical problem that needs to be solved urgently. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a high-reliability polymer dielectric material, a planar capacitor material containing the material and a method for preparing the same, which can effectively reduce the number of pores in the dielectric layer of the chip capacitor material, thereby effectively improving the yield of the chip capacitor material and improving the withstand voltage characteristics.
[0004] The present invention provides a method for preparing a high-reliability polymer dielectric material, a planar capacitor material containing the material and a method for preparing the same, the method comprising providing an inorganic filler, a matrix material, a first auxiliary agent, a second auxiliary agent and a solvent;
[0005] Dissolving the inorganic filler and the first auxiliary agent in the solvent and mixing them evenly to form a first mixed liquid;
[0006] Dissolving the base material and the second auxiliary agent in the solvent, and mixing them evenly to form a second mixed liquid;
[0007] The first mixed liquid and the second mixed liquid are uniformly mixed in a weight ratio of 1:1 to 60:1 to form the polymer dielectric material;
[0008] The polymer dielectric material is subjected to negative pressure treatment to remove bubbles in the polymer dielectric material.
[0009] Furthermore, the inorganic filler includes at least one of sodium barium titanate, barium titanate, calcium copper titanate, calcium copper titanate, strontium titanate, strontium titanate, strontium titanate, barium strontium titanate, calcium titanate, calcium titanate, barium calcium titanate, calcium barium titanate, lead zirconate titanate, sodium lead titanate, lead titanate and lead titanate.
[0010] Furthermore, the matrix material includes at least one of glycidyl ether epoxy resin, glycidyl ester epoxy resin, bisphenol A epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, epoxidized olefin compound, sugarcane polyol epoxy resin and mixed structure epoxy resin.
[0011] Furthermore, the first auxiliary agent includes at least one of a curing agent and a dispersant; the second auxiliary agent includes at least one of a curing agent, a dispersant, a coupling agent, a leveling agent, a defoaming agent, and a accelerator.
[0012] Furthermore, the solvent includes at least two of acetone, pentanone, anhydrous ethanol, butanone, cyclohexanone, isopropyl ketone and ethyl acetate.
[0013] Furthermore, dissolving the inorganic filler and the first auxiliary agent in the solvent includes: mixing the inorganic filler, the first auxiliary agent and the solvent, and then preparing the first mixed solution by ball milling, wherein the ball milling speed is 100 to 300 revolutions per minute and the ball milling time is 12 to 40 hours.
[0014] Furthermore, dissolving the base material and the second auxiliary agent in the solvent includes: dissolving the base material and the second auxiliary agent in the solvent by stirring, and the stirring method adopted is at least one of ultrasonic stirring and magnetic stirring, wherein the stirring temperature is 0 to 40° C., and the stirring time is 5 to 35 minutes.
[0015] Furthermore, the polymer dielectric material slurry is subjected to negative pressure treatment in a negative pressure environment of -0.05 MPa to -0.10 MPa.
[0016] Furthermore, the polymer dielectric material slurry is treated under negative pressure for a period of 1 min to 60 min.
[0017] The present invention also provides a method for manufacturing a planar capacitor material, comprising:
[0018] Providing a first electrode layer, a second electrode layer, and the polymer dielectric material obtained according to the method for manufacturing a high-reliability polymer dielectric material according to any one of claims 1 to 7;
[0019] Applying the polymer dielectric material on the surface of the first electrode layer to form a semi-cured polymer dielectric material layer on the surface of the first electrode layer;
[0020] The semi-cured polymer dielectric material layer is sandwiched between the first electrode layer and the second electrode layer, and the semi-cured polymer dielectric material layer is dried to cure the semi-cured polymer dielectric material layer and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0021] Furthermore, the planar capacitor material is manufactured by the above-mentioned method for manufacturing the planar capacitor material.
[0022] The invention provides a method for manufacturing a high-reliability polymer dielectric material, a planar capacitor material containing the material, and a method for manufacturing the same. By subjecting the polymer dielectric material to negative pressure treatment, bubbles in the polymer dielectric material are reduced or eliminated, thereby effectively solving the problem that the polymer dielectric material containing pores as a dielectric layer changes the capacitance performance of the chip capacitor material (such as reduced withstand voltage characteristics, reduced capacitance value, reduced peel strength, etc.), leading to functional failure of electronic products. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The figure is a schematic flow chart of the method for manufacturing the high-reliability polymer dielectric material of the present invention.
[0024] Figure 2 It is a schematic diagram of the method for manufacturing the planar capacitor material of the present invention. DETAILED DESCRIPTION
[0025] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0026] The terms "first", "second", "third", "fourth" and the like in the description and claims of the present invention are used to distinguish similar objects and are not necessarily used to describe a particular order or sequence.
[0027] Figure 1 This is a schematic diagram of the process for preparing the high reliability polymer dielectric material of the present invention. Figure 1 , a method for making a high reliability polymer dielectric material comprises:
[0028] Providing inorganic filler, matrix material, first auxiliary agent, second auxiliary agent and solvent;
[0029] The inorganic filler and the first auxiliary agent are dissolved in a solvent and mixed evenly to form a first mixed solution. Specifically, after the inorganic filler, the first auxiliary agent and the solvent are mixed, the first mixed solution is prepared by ball milling, wherein the ball milling speed is 100 to 300 revolutions per minute and the ball milling time is 12 to 40 hours.
[0030] The base material and the second auxiliary agent are dissolved in the solvent and mixed evenly to form a second mixed liquid. Specifically, the base material and the second auxiliary agent are dissolved in the solvent by stirring. The stirring method adopted is at least one of ultrasonic stirring and magnetic stirring, wherein the stirring temperature is 0 to 40° C. and the stirring time is 5 to 35 minutes.
[0031] The first mixed liquid and the second mixed liquid are uniformly mixed in a weight ratio of 1:1 to 60:1 to form the polymer dielectric material;
[0032] The polymer dielectric material is placed in a negative pressure environment of -0.05Mpa to -0.10Mpa for negative pressure treatment, thereby eliminating bubbles in the polymer dielectric material.
[0033] The first mixed liquid and the second mixed liquid are uniformly mixed in a weight ratio of 1:1 to 60:1, for example, 1:1, 1.5:1, 5:1, 5.5:1, 10:1, 10.5:1, 15:1, 15.5:1, 20:1, 20.5:1, 25:1, 25.5:1, 30:1, 30.5:1, 35:1, 35.5:1, 40:1, 45:1, 45.5:1, 50:1, 50.5:1, 55.5:1, 60:1;
[0034] The solid content of the polymer dielectric material slurry is 20% to 80%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%;
[0035] The viscosity of the polymer dielectric material is 2 to 500 centipoise, for example, 2 centipoise, 3 centipoise, 5 centipoise, 7 centipoise, 9 centipoise, 10 centipoise, 20 centipoise, 30 centipoise, 40 centipoise, 50 centipoise, 60 centipoise, 70 centipoise, 80 centipoise, 90 centipoise, 100 centipoise, 200 centipoise, 300 centipoise, 400 centipoise, 450 centipoise, 460 centipoise, 470 centipoise, 480 centipoise, 490 centipoise, 500 centipoise;
[0036] The pressure value of the negative pressure environment is -0.05Mpa to -0.10Mpa, for example, -0.08Mpa, -0.09Mpa, and -0.10Mpa.
[0037] The time of negative pressure treatment is 1 minute, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, and 60 minutes.
[0038] The method for producing a high-reliability polymer dielectric material of the present invention can produce a high-reliability polymer dielectric material without pores.
[0039] Optionally, the inorganic filler includes at least one of sodium barium titanate, barium titanate, calcium copper titanate, calcium copper titanate, strontium titanate, strontium titanate, strontium titanate, barium strontium titanate, calcium titanate, calcium titanate, barium calcium titanate, calcium barium titanate, lead zirconate titanate, sodium lead titanate, lead titanate and lead titanate.
[0040] Optionally, the matrix material includes at least one of resins including glycidyl ether epoxy resin, glycidyl ester epoxy resin, bisphenol A epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, epoxidized olefin compound, sugarcane polyol epoxy resin and mixed structure epoxy resin.
[0041] Optionally, the first auxiliary agent includes at least one of a curing agent and a dispersant; and the second auxiliary agent includes at least one of a curing agent, a dispersant, a coupling agent, a leveling agent, a defoaming agent, and a accelerator.
[0042] Optionally, the solvent includes at least two of acetone, pentanone, anhydrous ethanol, butanone, cyclohexanone, isopropyl ketone, and ethyl acetate.
[0043] Figure 2 is a schematic flow chart of a method for making a planar capacitor material of the present invention. The present invention also relates to a method for making a planar capacitor material, such as Figure 2 As shown, the method for making the planar capacitor material includes:
[0044] Providing a first electrode layer, a second electrode layer, and a polymer dielectric material obtained according to the method for manufacturing the polymer dielectric material with high reliability;
[0045] Applying a polymer dielectric material on the surface of the first electrode layer to form a semi-cured polymer dielectric material layer on the surface of the first electrode layer;
[0046] A semi-cured polymer dielectric material layer is sandwiched between a first electrode layer and a second electrode layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0047] Optionally, the drying process uses a drying temperature of 40° C. to 170° C. and a drying time of 6 to 40 hours.
[0048] Optionally, the dielectric constant of the polymer dielectric material in the planar capacitor material is 8-40, for example, 10, 12, 14, 16, 20, 25, 30, or 35.
[0049] Optionally, the dielectric loss of the polymer dielectric material in the planar capacitor material is less than or equal to 0.05.
[0050] Optionally, the dielectric layer of the planar capacitor material has a thickness of 1 μm to 50 μm, for example, 2 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 20 μm, 30 μm, 40 μm, or 50 μm.
[0051] In particular, when the liquid slurry of polymer dielectric material used for planar capacitor materials is placed in a negative pressure environment of -0.088Mp to -0.092Mpa, the negative pressure time is related to the liquid level height of the slurry glue during 1-15 minutes, and has a positive effect on the number of pores in the polymer dielectric material slurry and the voltage resistance performance of the planar capacitor material; during 15-60 minutes, the negative pressure time will have a negative effect on the peel strength (bonding strength between the polymer dielectric material and the electrode layer) performance of the planar capacitor material, and may even cause delamination and detachment.
[0052] Example 1
[0053] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0054] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0055] The first mixed liquid and the second mixed liquid are mixed in a mass ratio of 10:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry has a solid content of 65.6% and a viscosity of 6-7 cps.
[0056] providing a first electrode layer and a second electrode layer;
[0057] Applying the polymer dielectric material on the surface of the first electrode layer to form a semi-cured first polymer dielectric material layer on the surface of the first electrode layer;
[0058] Applying the polymer dielectric material on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0059] The slurry is applied to the first electrode layer and the second electrode layer in an area of 250 mm*100 mm, and the thickness is 8 um.
[0060] The first electrode layer and the second electrode layer coated with the polymer dielectric material were tested respectively, and the number of pores was found to be 7 to 8.
[0061] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0062] The thickness of the dielectric layer of the polymer dielectric material is 16 um. The planar capacitor was tested and failed the 100 V withstand voltage test. The dielectric constant was measured to be 15.98 at a frequency of 1000 Hz, and the dielectric loss was 0.0151.
[0063] Example 2
[0064] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0065] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0066] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 10:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 65.6% and a viscosity of 6-7 cps.
[0067] The polymer dielectric material slurry with a mass of 100 g and a liquid level of 2 cm was placed in a negative pressure device with a pressure value of -0.090 MPa for 5 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0068] providing a first electrode layer and a second electrode layer;
[0069] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0070] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0071] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 8 um.
[0072] The first electrode layer and the second electrode layer were tested respectively, and it was found that the number of pores therein was 3 to 4.
[0073] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0074] The thickness of the dielectric layer of the polymer dielectric material is 16 um. The planar capacitor was tested and failed the 100 V withstand voltage test. The dielectric constant was measured to be 15.87 at a frequency of 1000 Hz, and the dielectric loss was 0.0154.
[0075] Example 3
[0076] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0077] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0078] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 10:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 65.6% and a viscosity of 6-7 cps.
[0079] The polymer dielectric material slurry with a mass of 100 g and a liquid level of 2 cm was placed in a negative pressure device with a pressure value of -0.090 MPa for 10 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0080] providing a first electrode layer and a second electrode layer;
[0081] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0082] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0083] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 8 um.
[0084] The first electrode layer and the second electrode layer were tested respectively, and the number of pores therein was found to be 0.
[0085] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0086] The thickness of the dielectric layer of the polymer dielectric material is 16um. The planar capacitor was tested and passed the 100V withstand voltage. The dielectric constant was measured to be 16.29 at a frequency of 1000 Hz, and the dielectric loss was 0.0130. The peel strength of the planar capacitor material is greater than or equal to 0.7N / mm.
[0087] Example 4
[0088] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0089] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0090] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 10:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 65.6% and a viscosity of 6-7 cps.
[0091] The polymer dielectric material slurry with a mass of 100 g and a liquid level of 2 cm was placed in a negative pressure device with a pressure value of -0.090 MPa for 15 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0092] providing a first electrode layer and a second electrode layer;
[0093] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0094] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0095] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 8 um.
[0096] The first electrode layer and the second electrode layer were tested respectively, and the number of pores therein was found to be 0.
[0097] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0098] The thickness of the dielectric layer of the polymer dielectric material is 16um. The planar capacitor was tested and passed the 100V withstand voltage test. The dielectric constant was measured to be 16.57 at a frequency of 1000 Hz, and the dielectric loss was 0.0121. However, the peel strength of the planar capacitor material is only 0.1-0.3N / mm, and the electrode is very easy to delaminate and fall off. The reason for this phenomenon may be that some organic epoxy resins and curing agents accelerate the addition reaction in advance under long-term negative pressure conditions to form a cross-linked structure.
[0099] Example 5
[0100] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0101] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0102] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 10:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 65.6% and a viscosity of 6-7 cps.
[0103] The polymer dielectric material slurry with a mass of 250 g and a liquid level of 2 cm was placed in a negative pressure device with a pressure value of -0.092 MPa for 5 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0104] providing a first electrode layer and a second electrode layer;
[0105] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0106] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0107] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 8 um.
[0108] The first electrode layer and the second electrode layer were tested respectively, and it was found that the number of pores therein was 4.
[0109] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0110] The thickness of the dielectric layer of the polymer dielectric material is 16 um. The planar capacitor was tested and failed the 100 V withstand voltage test. The dielectric constant was measured to be 16.03 at a frequency of 1000 Hz, and the dielectric loss was 0.0124.
[0111] Example 6
[0112] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0113] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0114] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 10:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 65.6% and a viscosity of 6-7 cps.
[0115] The polymer dielectric material slurry with a mass of 250 g and a liquid level of 2 cm was placed in a negative pressure device with a pressure value of -0.092 MPa for 10 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0116] providing a first electrode layer and a second electrode layer;
[0117] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0118] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0119] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 8 um.
[0120] The first electrode layer and the second electrode layer were tested respectively, and the number of pores therein was found to be 0.
[0121] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0122] The thickness of the dielectric layer of the polymer dielectric material is 16um. The planar capacitor was tested and passed the 100V withstand voltage. The dielectric constant was measured to be 16.31 at a frequency of 1000 Hz, and the dielectric loss was 0.0173. The peel strength of the planar capacitor material is greater than or equal to 0.7N / mm.
[0123] Example 7
[0124] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0125] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0126] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 10:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 65.6% and a viscosity of 6-7 cps.
[0127] The polymer dielectric material slurry with a mass of 250 g and a liquid level of 2 cm was placed in a negative pressure device with a pressure value of -0.092 MPa for 15 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0128] providing a first electrode layer and a second electrode layer;
[0129] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0130] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0131] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 8 um.
[0132] The first electrode layer and the second electrode layer were tested respectively, and the number of pores therein was found to be 0.
[0133] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0134] The thickness of the dielectric layer of the polymer dielectric material is 16um. The planar capacitor was tested and passed the 100V withstand voltage. The dielectric constant was measured to be 16.86 at a frequency of 1000 Hz, and the dielectric loss was 0.0131; however, the peel strength of the planar capacitor material was only 0.1-0.2N / mm, and the electrode was very easy to delaminate and fall off.
[0135] Example 8
[0136] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0137] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0138] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 10:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 65.6% and a viscosity of 6-7 cps.
[0139] The polymer dielectric material slurry with a mass of 550 g and a liquid level of 4.5 cm was placed in a negative pressure device with a pressure value of -0.092 MPa for 5 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0140] providing a first electrode layer and a second electrode layer;
[0141] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0142] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0143] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 8 um.
[0144] The first electrode layer and the second electrode layer were tested respectively, and it was found that the number of pores therein was 3.
[0145] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0146] The thickness of the dielectric layer of the polymer dielectric material is 16 um. The planar capacitor was tested and failed the 100 V withstand voltage test. The dielectric constant was measured to be 16.57 at a frequency of 1000 Hz, and the dielectric loss was 0.0121.
[0147] Example 9
[0148] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0149] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0150] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 10:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 65.6% and a viscosity of 6-7 cps.
[0151] The polymer dielectric material slurry with a mass of 550 g and a liquid level of 4.5 cm was placed in a negative pressure device with a pressure value of -0.092 MPa for 10 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0152] providing a first electrode layer and a second electrode layer;
[0153] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0154] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0155] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 8 um.
[0156] The first electrode layer and the second electrode layer were tested respectively, and it was found that the number of pores therein was 1.
[0157] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0158] The thickness of the dielectric layer of the polymer dielectric material is 16 um. The planar capacitor was tested and failed to pass the 100 V withstand voltage. The dielectric constant was measured to be 16.05 at a frequency of 1000 Hz, and the dielectric loss was 0.0140.
[0159] Example 10
[0160] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0161] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0162] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 10:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 65.6% and a viscosity of 6-7 cps.
[0163] The polymer dielectric material slurry with a mass of 550 g and a liquid level of 4.5 cm was placed in a negative pressure device with a pressure value of -0.092 MPa for 15 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0164] providing a first electrode layer and a second electrode layer;
[0165] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0166] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0167] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 8 um.
[0168] The first electrode layer and the second electrode layer were tested respectively, and the number of pores therein was found to be 0.
[0169] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0170] The thickness of the dielectric layer of the polymer dielectric material is 16 um. The planar capacitors are tested and all pass the 100 V withstand voltage test. The dielectric constant is measured to be 16.05 at a frequency of 1000 Hz, and the dielectric loss is 0.0163.
[0171] Embodiment 11
[0172] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0173] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0174] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 16:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 64.4% and a viscosity of 4-5 cps.
[0175] providing a first electrode layer and a second electrode layer;
[0176] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0177] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0178] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 6 um.
[0179] The first electrode layer and the second electrode layer were tested respectively, and the number of pores therein was found to be 8 to 9.
[0180] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0181] The thickness of the dielectric layer of the polymer dielectric material is 12 um. The planar capacitors were tested and failed to pass the 100V withstand voltage test. The dielectric constant was measured to be 23.17 at a frequency of 1000 Hz, and the dielectric loss was 0.0210.
[0182] Example 12
[0183] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0184] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0185] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 16:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 64.4% and a viscosity of 4-5 cps.
[0186] The polymer dielectric material slurry with a mass of 1.4 kg and a liquid level of 18 cm was placed in a negative pressure device with a pressure value of -0.088 MPa for 5 minutes to obtain a negative pressure treated polymer dielectric material slurry.
[0187] providing a first electrode layer and a second electrode layer;
[0188] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0189] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0190] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 6 um.
[0191] The first electrode layer and the second electrode layer were tested respectively, and it was found that the number of pores therein was 5.
[0192] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0193] The thickness of the dielectric layer of the polymer dielectric material is 12 um. The planar capacitor was tested and failed to pass the 100V withstand voltage. The dielectric constant was measured to be 23.38 at a frequency of 1000 Hz, and the dielectric loss was 0.0240.
[0194] Example 13
[0195] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0196] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0197] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 16:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 64.4% and a viscosity of 4-5 cps.
[0198] The polymer dielectric material slurry with a mass of 1.4 kg and a liquid level of 18 cm was placed in a negative pressure device with a pressure value of -0.088 MPa for 10 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0199] providing a first electrode layer and a second electrode layer;
[0200] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0201] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0202] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 6 um.
[0203] The first electrode layer and the second electrode layer were tested respectively, and it was found that the number of pores therein was 1.
[0204] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0205] The thickness of the dielectric layer of the polymer dielectric material is 12 um. The planar capacitor was tested and failed to pass the 100V withstand voltage. The dielectric constant was measured to be 23.24 at a frequency of 1000 Hz, and the dielectric loss was 0.0230.
[0206] Embodiment 14
[0207] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0208] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0209] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 16:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 64.4% and a viscosity of 4-5 cps.
[0210] The polymer dielectric material slurry with a mass of 1.4 kg and a liquid level of 18 cm was placed in a negative pressure device with a pressure value of -0.088 MPa for 15 minutes to obtain a negative pressure treated polymer dielectric material slurry.
[0211] providing a first electrode layer and a second electrode layer;
[0212] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0213] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0214] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 6 um.
[0215] The first electrode layer and the second electrode layer were tested respectively, and the number of pores therein was found to be 0.
[0216] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0217] The thickness of the dielectric layer of the polymer dielectric material is 12 um. The planar capacitors are tested and all pass the 100V withstand voltage test. The dielectric constant is measured to be 23.57 at a frequency of 1000 Hz, and the dielectric loss is 0.0210.
[0218] Embodiment 15
[0219] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0220] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0221] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 16:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 64.4% and a viscosity of 4-5 cps.
[0222] The polymer dielectric material slurry with a mass of 1.4 kg and a liquid level of 18 cm was placed in a negative pressure device with a pressure value of -0.092 MPa for 5 minutes to obtain a negative pressure treated polymer dielectric material slurry.
[0223] providing a first electrode layer and a second electrode layer;
[0224] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0225] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0226] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 6 um.
[0227] The first electrode layer and the second electrode layer were tested respectively, and it was found that the number of pores therein was 3.
[0228] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0229] The thickness of the dielectric layer of the polymer dielectric material is 12 um. The planar capacitor was tested and failed to pass the 100V withstand voltage. The dielectric constant was measured to be 23.41 at a frequency of 1000 Hz, and the dielectric loss was 0.0230.
[0230] Example 16
[0231] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0232] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0233] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 16:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 64.4% and a viscosity of 4-5 cps.
[0234] The polymer dielectric material slurry with a mass of 1.4 kg and a liquid level of 18 cm was placed in a negative pressure device with a pressure value of -0.092 MPa for 10 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0235] providing a first electrode layer and a second electrode layer;
[0236] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0237] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0238] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 6 um.
[0239] The first electrode layer and the second electrode layer were tested respectively, and it was found that the number of pores therein was 1.
[0240] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0241] The thickness of the dielectric layer of the polymer dielectric material is 12 um. The planar capacitor was tested and failed the 100 V withstand voltage test. The dielectric constant was measured to be 23.54 at a frequency of 1000 Hz, and the dielectric loss was 0.0210.
[0242] Embodiment 17
[0243] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0244] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0245] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 16:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 64.4% and a viscosity of 4-5 cps.
[0246] The polymer dielectric material slurry with a mass of 1.4 kg and a liquid level of 18 cm was placed in a negative pressure device with a pressure value of -0.092 MPa for 15 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0247] providing a first electrode layer and a second electrode layer;
[0248] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0249] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0250] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 6 um.
[0251] The first electrode layer and the second electrode layer were tested respectively, and the number of pores therein was found to be 0.
[0252] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0253] The thickness of the dielectric layer of the polymer dielectric material is 12um. The planar capacitor was tested and passed the 100V withstand voltage. The dielectric constant was measured to be 23.66 at a frequency of 1000 Hz, and the dielectric loss was 0.0220. The peel strength of the planar capacitor material is greater than or equal to 0.7N / mm.
[0254] Embodiment 18
[0255] The inorganic material barium titanate, the curing agent, and the dispersant accounting for 1% to 5% of the total mass of the first mixed solution are dissolved in a mixed solvent of anhydrous ethanol, butanone and ethyl acetate, and poured into a grinding tank, and ball-milled at a speed of 100 to 300 rpm for 24 hours to obtain the first mixed solution;
[0256] Dissolve bisphenol A epoxy resin and 1% to 5% of the auxiliary agent of the total mass of the second mixed solution in anhydrous ethanol and a mixed solvent of butanone and ethyl acetate, and stir for 5 minutes by magnetic stirring to obtain a second mixed solution.
[0257] The first mixed liquid and the second mixed liquid were stirred at a mass ratio of 16:1 to obtain a polymer dielectric material slurry, wherein the polymer dielectric material slurry had a solid content of 64.4% and a viscosity of 4-5 cps.
[0258] The polymer dielectric material slurry with a mass of 1.4 kg and a liquid level of 18 cm was placed in a negative pressure device with a pressure value of -0.092 MPa for 20 minutes of negative pressure treatment to obtain a polymer dielectric material slurry treated with negative pressure.
[0259] providing a first electrode layer and a second electrode layer;
[0260] Applying the polymer dielectric material slurry on the surface of the first electrode layer to form a semi-cured first polymer dielectric material medium layer on the surface of the first electrode layer;
[0261] Applying the polymer dielectric material slurry on the surface of the second electrode layer to form a semi-cured second polymer dielectric material layer on the surface of the second electrode layer;
[0262] The areas of the polymer dielectric material slurry coated on the first electrode layer and the second electrode layer are both 250 mm*100 mm, and the coating thickness is both 6 um.
[0263] The first electrode layer and the second electrode layer were tested respectively, and the number of pores therein was found to be 0.
[0264] The first polymer dielectric material layer and the second polymer dielectric material layer are laminated to form a polymer dielectric material layer, and the semi-cured polymer dielectric material layer is dried to cure and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
[0265] The thickness of the dielectric layer of the polymer dielectric material is 12um. The planar capacitor was tested and passed the 100V withstand voltage. The dielectric constant was measured to be 23.84 at a frequency of 1000 Hz, and the dielectric loss was 0.0240; however, the peel strength of the planar capacitor material was only 0.1-0.2N / mm, and the electrode was very easy to delaminate and fall off.
[0266] It can be seen from the above comparative examples that if the polymer dielectric material slurry is not subjected to any negative pressure treatment in Examples 1 and 11, a plurality of pores will be generated in the electrode layer coated with the polymer dielectric material. If the polymer dielectric material slurry is placed in a negative pressure environment for negative pressure treatment in Examples 2 to 10 and 12 to 18, and is observed by the control variable method, the number of pores in the electrode layer coated with the polymer dielectric material will decrease as the negative pressure treatment time increases, and when the negative pressure treatment time reaches a certain value, the pores in the electrode layer of the polymer dielectric material will disappear.
[0267] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for producing a high-reliability polymer dielectric material, characterized in that: The method comprises: Providing inorganic filler, matrix material, first auxiliary agent, second auxiliary agent and solvent; Dissolving the inorganic filler and the first auxiliary agent in the solvent and mixing them evenly to form a first mixed liquid; Dissolving the base material and the second auxiliary agent in the solvent, and mixing them evenly to form a second mixed liquid; The first mixed liquid and the second mixed liquid are uniformly mixed in a weight ratio of 1:1 to 60:1 to form the polymer dielectric material; The polymer dielectric material is subjected to negative pressure treatment to remove bubbles in the polymer dielectric material.
2. The method for manufacturing a high-reliability polymer dielectric material according to claim 1, characterized in that: The inorganic filler includes at least one of sodium barium titanate, barium titanate, calcium copper titanate, calcium copper titanate, strontium titanate, strontium titanate, strontium titanate, barium strontium titanate, calcium titanate, calcium titanate, barium calcium titanate, calcium barium titanate, lead zirconate titanate, sodium lead titanate, lead titanate and lead titanate.
3. The method for manufacturing a high-reliability polymer dielectric material according to claim 1, characterized in that: The matrix material includes at least one of glycidyl ether epoxy resin, glycidyl ester epoxy resin, bisphenol A epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, epoxidized olefin compound, sugarcane polyol epoxy resin and mixed structure epoxy resin.
4. The method for manufacturing a composite dielectric material according to claim 1, characterized in that: The first auxiliary agent includes at least one of a curing agent and a dispersant; the second auxiliary agent includes at least one of a curing agent, a dispersant, a coupling agent, a leveling agent, a defoaming agent, and a accelerator.
5. The method for manufacturing a high-reliability polymer dielectric material according to claim 1, wherein: The solvent includes at least two of acetone, pentanone, anhydrous ethanol, butanone, cyclohexanone, isopropyl ketone and ethyl acetate.
6. The method for manufacturing a high-reliability polymer dielectric material according to claim 1, characterized in that: The step of dissolving the inorganic filler and the first auxiliary agent in the solvent comprises: After the inorganic filler, the first auxiliary agent and the solvent are mixed, the first mixed solution is prepared by ball milling, wherein the ball milling speed is 100 to 300 revolutions per minute and the ball milling time is 12 to 40 hours.
7. The method for manufacturing a high-reliability polymer dielectric material according to claim 1, characterized in that: The step of dissolving the base material and the second auxiliary agent in the solvent comprises: The base material and the second auxiliary agent are dissolved in the solvent by stirring, and the stirring method adopted is at least one of ultrasonic stirring and magnetic stirring, wherein the stirring temperature is 0 to 40° C. and the stirring time is 5 to 35 minutes.
8. The method for manufacturing a high-reliability polymer dielectric material according to claim 1, characterized in that: The polymer dielectric material slurry is subjected to negative pressure treatment in a negative pressure environment of -0.05Mpa to -0.10Mpa.
9. A method for making a planar capacitor material, characterized in that include: Providing a first electrode layer, a second electrode layer, and the polymer dielectric material obtained according to the method for manufacturing a high-reliability polymer dielectric material according to any one of claims 1 to 8; Applying the polymer dielectric material on the surface of the first electrode layer to form a semi-cured polymer dielectric material layer on the surface of the first electrode layer; The semi-cured polymer dielectric material layer is sandwiched between the first electrode layer and the second electrode layer, and the semi-cured polymer dielectric material layer is dried to cure the semi-cured polymer dielectric material layer and adhere to the first electrode layer and the second electrode layer, thereby forming a planar capacitor material.
10. A planar capacitor material, characterized in that: The planar capacitor material is manufactured by the method for manufacturing the planar capacitor material according to claim 9.
Citation Information
Patent Citations
Method for manufacturing high dielectric composite thin film
CN103319736A
CAPACITOR and manufacturing method thereof
CN108806979A
Buried capacitor material, preparation method thereof and printed circuit board
CN110310829A
Manufacturing method and device of planar capacitor
CN111799106A
Manufacturing method and system of planar capacitor and planar capacitor
CN113658800A